Respon Penawaran dan Permintaan Pala Indonesia di Pasar Internasional - Orchida Indahwaty T; Djaimi Bakce; Novia Dewi (JURNAL AGRICA, 2023)
Indonesia is one of the largest nutmeg producing country globally, followed by Guatemala, India and Nepal. Indonesia also the world’s leading largest harvest area with the nutmeg exporter which accounts for significant part of the nutmeg demand approximately 31.03 percent of the world's nutmeg production. This study aims to analyzed the response of supply and demand for Indonesian nutmeg in the international market over the period of 1985-2019. Secondary data were collected from various sources, including FAO and World Bank. This research used an econometric approach by constructed simultaneous equation model. Result showed that responsive factors affecting supply and demand for Indonesian nutmeg in the short term were export and nutmeg production and in the long terms were fertilizer urea Indonesia price in the previous year, growth nutmeg harvested area, Indonesian nutmeg supply, exchange rate of US dollars, per capita income, and the world nutmeg prices. Recommended policy for the Government that Indonesian nutmeg can be developed through a program directed at improving the price and expanding the harvest area. As a result of this policy implication, nutmeg supply grew significantly. By raising the farm level nutmeg price, able to increasing  Indonesian nutmeg farmers' incomes affect to increasing their welfare.